Biodiversity characteristics of Teucrium polium species in Saudi Arabia - Bukhari, Najat A. (Saudi J Biol Sci, 2014)
Teucrium (Lamiaceae) is a large and polymorphic genus distributed mainly in Europe, North Africa and in the temperate parts of Asia. In this study, the anatomical features of the leaf and stem of Teucrium polium are investigated. Teucrium has 19 taxa in Iran, which mainly grow in the Irano-Turanian region between 700 and 2000 m above sea level. T. polium belonging to sect. Polium, is a perennial herb growing on Lorestan province. The leaves clearly exhibit xeromorphy due to features such as thick cuticle layer, thick outer epidermal cell wall, high density of trichomes and thick palisade layer of the mesophyll. Anatomical studies on T. polium revealed that the stem shares the general characteristics of the Labiatae family. The aim of our approach was to study the morphological and taxonomical parameters for T. polium in Saudi Arabia. The results of this study showed that there was no influence of environment on the structure of stomata and trichomes as studying species with T.polium. In conclusion our study shows we have studied the geographical distribution of the species in Saudi Arabia and in the world.